Adsorption potential of kenaf for copper and nickel removal from aqueous solution - Zadeh, Maryam Rahmati (2010)
Heavy metal pollution is one of the environmental issues that become a concern due to their toxic effect to environment and human health. Adsorption has been widely used to remove heavy metals from industrial wastewater. Therefore, there is a need to explore new sources of an alternative and inexpensive adsorbent for elimination of heavy metals. In this study, a series of batch experiment was conducted to study the adsorption potential of kenaf as a biosorbent for Cu (II) and Ni (II) removal from aqueous solutions. The specific objectives are to obtain adsorption isotherms, kinetics determination, and measure the adsorption capacity in batch and fixed bed column system. The single adsorption isotherm and kinetics were carried out at a constant temperature of 30+1°C using an incubator shaker operated at 200 rpm. Some of the parameters that affect the adsorption process such as pH, initial concentration of adsorbate, adsorbent dosage and contact time was determined. The column study experiment was conducted with 100 mg/L of individual heavy metal solution. The effect of bed depth was examined with a flow rate of 6 mL/min and different bed depths of 15, 20, 25 and 30 cm to obtain the adsorption capacity and exhaustion time by evaluating the breakthrough curves. Also, to determine the effect of different flow rates, the column study experiment was conducted at a constant bed depth (20 cm) with different flow rates of 4, 6, and 9 mL/min.